OPTIMIZING THE USE OF TECHNOLOGY IN CREATING CLIMATE SMART AGRICULTURE - Salawati, Umi; Rusmayadi, Gusti; Pareira, Magdalena Sunarty; Tahir, Usman; Sutiharni, Sutiharni (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Agriculture is an important sector for Indonesia. Because around 30% of the population works in the agricultural industry. Currently, agricultural conditions in Indonesia are facing challenges due to climate anomalies. Unpredictable climate changes, shorter growing seasons, an increase in pests and diseases and these conditions have an impact on increasing production costs while yields are not optimal. Climate change is one of the obstacles in increasing plant productivity. The negative impacts of extreme global climate change include the degradation of land and water resources, damage to agricultural and irrigation infrastructure, the emergence of floods and droughts, and increased attacks by pests and plant diseases. Therefore, farmers need knowledge and farming skills that are adaptive to climate change or what is known as Climate Smart Agriculture (CSA). Climate Smart Agriculture is a useful approach to guide the actions needed to transform and reorient agricultural systems to effectively support development and ensure food security in conditions of climate change. CSA technology focuses on climate resilience and food security with the main objectives being: 1.) Increasing agricultural productivity and income in a sustainable manner, 2.) Adapting and building food security to climate change, 3.) Reducing and minimizing greenhouse gas emissions (Mitigation), 4.) Optimizing the use of various resources. So it is hoped that optimal results will be obtained in the agricultural sector. This research is qualitative research with a descriptive approach. The researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions. Keywords: Climate Smart Agriculture, Climate Change, Modern Agriculture